International banking and foreign trade : institutions, policies and practices in the Western Hemisphere - International Banking Summer School (London : Published for the Graduate School of Banking (American Bankers Association) and the Institute of Bankers by Europa Publications, 1956)
This book contains lectures delivered by scholars on the subject matter of International Banking and Foreign Trade, largely from the point of view of the European continent.
usc 30/06/2017
Loans
Keywords: Commerce; Currency question; Foreign exchange